Transformational Leadership and Work Discipline as Determinants of Employee Performance in the Digital Marketing Industry: Evidence from CV. Queensha Media Group - Erlando Selsep Gumelar; Siti Maryam (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The rapid growth of the digital marketing industry requires organizations to strengthen employee performance through effective leadership and organizational discipline in increasingly dynamic, creativity-oriented, and technology-driven work environments. This study aims to analyze the influence of transformational leadership and work discipline on employee performance at CV. Queensha Media Group and examine their explanatory power within the context of the digital marketing industry. This research employed a quantitative associative approach using a saturated sampling technique involving all 120 employees, while data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The measurement model demonstrated satisfactory validity and reliability, whereas the structural model produced a substantial explanatory power (R² = 0.819). The findings reveal that transformational leadership has a positive and significant effect on employee performance (β = 0.512; t = 5.728; p < 0.001), followed by work discipline (β = 0.461; t = 5.063; p < 0.001), indicating that transformational leadership is the more dominant determinant. These findings suggest that inspirational leadership is particularly effective in project-based, collaborative, and innovation-driven digital marketing organizations, while work discipline supports operational consistency through timely task completion and accountability. The study extends the empirical application of Human Resource Management theory by confirming the complementary roles of motivational leadership and behavioral control in enhancing employee performance and provides practical implications for strengthening leadership development, adaptive work discipline, and project management practices to improve organizational competitiveness in the digital marketing industry.